Analysis of Productivity using The Marvin E. Mundel Method - Meldia Fitri; Zefri Yenni; Celvin Adryanda (Jurnal Teknologi, 2022)
This study addressed the measurement of total productivity and the measurement of productivity for every input with the use of the method of Marvin E. Mundel. Then give the proposal on how the method enhancement productivity. The case study chosen involved a company in bread production in the urban area in the City of Padang, West Sumatera, Indonesia. These results prove the total productivity of the company tends abnormal, with the highest total production in March of 3.28% and the lowest total productivity in May was -6,07%. For results measurement productivity on input, the value is on income employee highest productivity in December was 15, 56%, and the lowest productivity in March amounted to -3,78%. Energy’s highest productivity in April was 11.48%, and the lowest productivity in May amounted to -13,08%. Raw ingredients' highest productivity in April was 11.23%, and the lowest productivity in May amounted to -7,28%. Depreciation cost’s highest productivity in August was 29.96%, and otherwise, the lowest productivity in May amounted to -79,46%. Transportation's highest productivity in December is by 15,56% as well as otherwise the lowest productivity in April amounted to -3,78%. And for enhancement of productivity with method give a proposal on each input. The conclusion from the productivity measurement on the company tends to be not stable. Productivity on value energy, raw materials, and costs depreciation experience a very significant decrease so that the need enhancement productivity with a suggestion for each input.